Empirical approaches to cognitive linguistics : analyzing real-life data - Luodonp?a?a-Manni, Milla; Penttil?a, Esa; Viimaranta, Johanna (Cambridge Scholars Publishing, 2017)
This collection takes a cognitive linguistic view on analyzing language and presents innovative contemporary Finnish research to the international audience. The volume brings together nine chapters presenting empirical case studies that rely on various kinds of corpus data and experimental data or combine both types of empirical evidence. The topics vary from semantics to grammatical description, from terminological choices to language acquisition, and they study language from perspectives as diverse as psycholinguistics, comparative linguistics, and translation studies. A multi-methodological.